Efektivitas Video Interaktif Keragaman Makanan Tradisional Sumatera dalam Meningkatkan Keterampilan Menyusun Kata pada Siswa Fase A - Agustin, Nur Imama Dwi; Istiq’faroh, Nurul; Herdiansyah, Rachma Adila (CV. Kurnia Grup, 2026)
This study aims to analyze the effectiveness of using interactive videos based on the diversity of traditional Sumatran foods in improving the early writing skills of elementary school students in Phase A. This study used a quantitative approach with a One Group Pretest-Posttest design. The subjects were 12 first-grade students of Lidah Wetan 4 Elementary School, Surabaya. Data collection techniques were carried out through pretests and posttests, while data analysis used normality tests, Wilcoxon Signed Rank Tests, and N-Gain tests. The results showed that the data were not normally distributed, so non-parametric tests were used. The Wilcoxon test results showed a significance value of 0.002 (<0.05), indicating a significant difference between the pretest and posttest results. In addition, the N-Gain test results showed an average value of 0.8047, which is included in the high category. This indicates that the use of interactive videos is effective in improving students' early writing skills. Thus, interactive video media based on local cultural contexts can be an innovative, interesting, and meaningful learning alternative to support the development of early literacy in elementary school students.